Climate change has increased the odds of extreme regional forest fire years globally - Abatzoglou, John T.; Kolden, Crystal A.; Cullen, Alison C.; Sadegh, Mojtaba; Williams, Emily L.; Turco, Marco; Jones, Matthew W. (Nature communications, 2025)
Regions across the globe have experienced devastating fire years in the past decade with far-reaching impacts. Here, we examine the role of antecedent and concurrent climate variability in enabling extreme regional fire years across global forests. These extreme years commonly coincided with extreme (1-in-15-year) fire weather indices (FWI) and featured a four and five-fold increase in the number of large fires and fire carbon emissions, respectively, compared with non-extreme years. Years with such extreme FWI metrics are 88-152% more likely across global forested lands under a contemporary (2011–2040) climate compared to a quasi-preindustrial (1851–1900) climate, with the most pronounced increased risk in temperate and Amazonian forests. Our results show that human-caused climate change is raising the odds of extreme climate-driven fire years across forested regions of the globe, necessitating proactive measures to mitigate risks and adapt to extreme fire years. The authors show that extreme fire years in global forests align with rare fire weather extremes. Climate change has made such extremes 88-152% more probable. These findings highlight the need for action towards adaptation and mitigation of fire impacts.